STRATEGIES OF AKIDAH AND AKHLAK TEACHERS IN ADDRESSING BULLYING USING THE BEHAVIORAL METHOD AT MADRASAH TSANAWIYAH BI’RUL ULUM GEDANGAN SIDOARJO - Eka Putri, Rahma; Ghozali, Solchan (PT. Antis International Publisher, 2025)
Objective: The research aims to mitigate bullying behaviors through targeted behavioral techniques and improve the psychological well-being of students. Method: Employing a qualitative design, the study utilizes non-participant observations, interviews, and document analysis to systematically collect, organize, and analyze data on bullying manifestations. Results: Findings reveal that bullying is predominantly expressed through physical aggression such as assault, punishment, and hitting, which adversely affect students’ mental health. However, school interventions—including anti-bullying strategies, risk mitigation efforts, and the integration of self-development curricula within Akidah and Akhlak lessons—have resulted in notable positive behavioral changes among students. Novelty: This research introduces a novel application of behavioral methods within a religious educational context, offering valuable insights into effective strategies for reducing bullying while reinforcing moral and ethical teachings in academic settings.